2019
DOI: 10.1111/imj.14184
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in patients with diabetic foot infections: a prospective cohort study

Abstract: Background An increasing prevalence of diabetes mellitus has led to a high risk of diabetic foot infections (DFI) and associated morbidity. However, little is known about the relationship between DFI and mortality. Aim To investigate the risk of mortality and associated factors in patients with DFI in an Australian context. Methods A prospective cohort study of inpatients with DFI between May 2012 and October 2016 was done at Royal Darwin Hospital, a tertiary referral hospital for the Top End of the Northern T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…7,8 The risk of mortality following admission of patients with diabetic foot infection is 8.9% in 1 year. 9 Probably in our patient, MRSA infection was also due to his previous hospitalisations that allowed selection and acquisition of antibiotic-resistant bacteria. 10 The presence of peripheral neuropathy allows the appearance of minor injuries, such as ingrown toenails, calluses, cuts, blisters and burns, to provide a strong incentive for the development of diabetic foot infections.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…7,8 The risk of mortality following admission of patients with diabetic foot infection is 8.9% in 1 year. 9 Probably in our patient, MRSA infection was also due to his previous hospitalisations that allowed selection and acquisition of antibiotic-resistant bacteria. 10 The presence of peripheral neuropathy allows the appearance of minor injuries, such as ingrown toenails, calluses, cuts, blisters and burns, to provide a strong incentive for the development of diabetic foot infections.…”
Section: Discussionmentioning
confidence: 77%
“…In particular, in accordance with the guidelines for diabetic foot infection, debridement of the wound was performed in a timely manner. 9 Daptomycin and rifampicin demonstrated to be the appropriate antibiotics to treat the MRSA wound infection within 2 weeks. Then, at home, daptomycin was switched to teicoplanin, another first-line anti-MRSA agent, to ensure the therapeutic continuity and avoid relapses.…”
Section: Discussionmentioning
confidence: 99%
“…Foryoung et al in Cameroon, Boyco et al in the US, Katz et al in Israel and Lynar et al in Australia reported similar ndings. 5,11,26,27 This nding may be explained by the fact that the prevalence of medical comorbidities that may lead to organ dysfunctions and death tend to increase with advancing age. Furthermore, micro and macrovascular diabetes complications are usually more life-threatening when they present in older than younger persons.…”
Section: Discussionmentioning
confidence: 99%
“…Foryoung et al from Cameroon, Boyco et al from the US, Katze from Israel and Lynar from Australia reported similar findings. 5,11,24,25 This finding may be explained by the fact that the prevalence of medical comorbidities that may lead to organ dysfunctions and death tend to increase with advancing age. Furthermore, micro and macrovascular diabetes complications are usually more life-threatening when they present in older than younger persons.…”
Section: Discussionmentioning
confidence: 99%